Chemical Prevention and Control of the Green Tide and Fouling Organism Ulva: Key Chemicals, Mechanisms, and Applications - Tang, Tao; Effiong, Kokoette; Hu, Jing; Li, Chao; Xiao, Xi (Frontiers in Marine Science, 2021)
The green algae, Ulva spp., have been causing environmental problems around the world, e.g. green tides and biofoulings. Green tides resulting from bloom floating Ulva have caused huge economic losses. Ulva foulings do not only increase the maintenance cost of marine facilities but also contribute to the biomass of floating algae which may induce green tide. Chemical methods are in general very cheap and convenient. In this paper, classical chemical methods that have been or are in use, and emerging chemical methods under research are systematically reviewed, and the advantages, disadvantages, mechanism and application of these methods are also summarized. Highly toxic reagents are used in classical chemical methods, including oxidants, acids, heavy metal compounds and synthetic biocides directly used or applied in antifouling coatings, aimed at killing or inhibiting Ulva effectively. However, these toxic reagents have high risk of resulting in secondary environmental problems. In order to minimize additional environmental impacts while solving the current problem, emerging and environmentally friendly chemical methods have been developed, such as the utilization of degradable natural products (mainly allelochemicals) and semi-natural products for Ulva inhibition and fouling control, and the use of flocculating agents to prevent microscopic propagules from germinating. All these chemical methods provide a promising direction for the prevention and control of Ulva.